The Subversion of Traditional Value System Built into Language in Joyce's Portrait and Kamov's Dried-Up Bog - Gjurgjan, Ljiljana Ina (1984)
The text shows how on the surface Joyce's Portrait follows the traditional teleological narration, but subverts it on the metaphorical pole expressing a constant indeterminacy and reluctance. Kamov uses the same procedure in Dried-Up Bog, but in a more radical way, evidently refusing the style of the realist novel and thus creating the first existential anti-hero in Croatian literature.
Literary Interrelations: Ireland, England, and the World ; Wolfgang Zach, Heinz Kosok, (Eds.) ; Tubingen : Gunter Narr Verlag, 1987. ; pp 57-65 ; Pretisak u Most
Projekt MZOS
ENG